LongTerm Outcomes of Three-Port Laparoscopic Right Hemicolectomy Versus Five-Port Laparoscopic Right Hemicolectomy: A Retrospective Study - Zhang, Tao; Zhang, Yaqi; Shen, Xiaonan; Shi, Yi; Ji, Xiaopin; Wang, Shaodong; Song, Zijia; Jing, Xiaoqian; Ye, Feng; Zhao, Ren (Frontiers in Oncology, 2021)
Purpose The aim of this study is to compare the long-term outcomes of three-port laparoscopic right hemicolectomy (TPLRC) and five-port laparoscopic right hemicolectomy (FPLRC) with retrospective analysis. Methods A total of 182 patients who accepted laparoscopic right hemicolectomy with either three ports (86 patients) or five ports (96 patients) from January 2012 to June 2017 were non-randomly selected and analyzed retrospectively. Results More lymph nodes were harvested in the TPLRC group than in the FPLRC group [17.5 (7), 14 (8) ml, p < 0.001]. There was less blood loss in the TPLRC group [50 (80) vs. 100 (125) ml, p = 0.015]. There were no significant differences in the other short-term or oncological outcomes between the two groups. The overall survival and disease-free survival were equivalent. Conclusions TPLRC is recommendable as it guarantees short- and long-term equivalent outcomes compared with FPLRC.